(untitled) (Journal for Studies in Humanities and Social Sciences, 2016)
Employees’ loyalty is shifting from loyalty towards the organisation to loyalty to the dollar (pay/benefits). There is no sense of pride in their membership of a certain organisation, joy is focused on the benefits an organisation offers and what’s in it for me attitude (employee). Job embeddedness is defined as a construct that deals with a broad array of influences that represents why an employee wants to stay with a specific organisation. Turnover intention can be defined as an employee’s intention to leave his/her job within a certain period of time. When employees experience a good fit, positive links and low sacrifices in their jobs, they are less likely to leave the organisation. Participants were made of 90 (48.1%) teachers from primary schools and 97 (51.9%) legal firm employees. Female employees from legal firms experienced higher levels of turnover intention than any other group. Divorced and single employees from the legal firms experienced significantly higher levels of turnover intention with married employees experiencing the lowest levels of turnover intention. Total turnover intention recorded a negative co-relation with overall job embeddedness (r=-.29*, p < 0.05), a positive co-relation with community job embeddedness (r=.02, p < 0.05) and health care and retirement job embeddedness (r=.14*, p < 0.05). Investing in team building activities, social events for staff members, paying the best competitive salaries and benefits, retaining the more competent employees within the profession will allow the organisation to prosper. Having the best and happiest employees within the market will allow organisations to meet the top two objectives of the organisation, maintain high levels of productivity and retain the best talent.